Treatment responses to antiangiogenetic therapy and chemotherapy in nonsecreting paraganglioma (PGL4) of urinary bladder with SDHB mutation: A case report. Issue 30 (July 2018) - Stigliano, Antonio; Lardo, Pina; Cerquetti, Lidia; Aschelter, Anna Maria; Matarazzo, Iolanda; Capriotti, Gabriela; Schiavi, Francesca; Marchetti, Paolo; Nardone, Maria Rosaria; Petrangeli, Elisa; Toscano, Vincenzo
Abstract: Introduction: Paraganglioma (PGL) is a rare neuroendocrine tumor. Currently, the malignancy is defined as the presence of metastatic spread at presentation or during follow-up. Several gene mutations are listed in the pathogenesis of PGL, among which succinate dehydrogenase (SDHX), particularly the SDHB isoform, is the main gene involved in malignancy. A 55-year-old male without evidence of catecholamine secretion had surgery for PGL of the urinary bladder. After 1 year, he showed a relapse of disease and demonstrated malignant PGL without evidence of catecholamine secretion with a germline heterozygous mutation of succinate dehydrogenase B (SDHB). After failure of a second surgery for relapse, he started medical treatment with sunitinib daily but discontinued due to serious side effects. Cyclophosphamide, vincristine, and dacarbazine (CVD) chemotherapeutic regimen stopped the disease progression for 7 months. Conclusion: Malignant PGL is a very rare tumor, and SDHB mutations must be always considered in molecular diagnosis because they represent a critical event in the progression of the oncological disease. Currently, there are few therapeutic protocols, and it is often difficult, as this case demonstrates, to decide on a treatment option according to a reasoned set of choices.